2009
DOI: 10.1016/j.ydbio.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the prechordal plate and patterning of the anteroposterior regional specificity of the involuting and extending archenteron roof of a urodele, Cynops pyrrhogaster

Abstract: We analyzed the notochord formation, formation of the prechordal plate, and patterning of anteroposterior regional specificity of the involuting and extending archenteron roof of a urodele, Cynops pyrrhogaster. The lower (LDMZ) and upper (UDMZ) domains of the dorsal marginal zone (DMZ) of the early gastrula involuted and formed two distinct domains: the anterior fore-notochordal endodermal roof and the posterior domain containing the prospective notochord. Cygsc is expressed in the LDMZ from the onset of gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The ring-shaped expression of Brachyury in the blastula marginal zone disappears, to be replaced later by expression in the constricting blastopore; still later, after blastopore closure, Brachyury expression appears in the prospective notochord, suggesting that a tri-phasic Brachyury expression pattern could be ancestral for anurans. In the urodeles Cynops and Ambystoma, Brachyury is expressed late, after the Gscexpressing anterior mesoderm has involuted, but in time for the involution of the Brachyury-expressing posterior mesoderm (Kaneda et al, 2009;Swiers et al, 2010). It remains to be determined, however, whether a role in germ layer internalization is indeed a common feature of the amphibian or even the metazoan Brachyury gene.…”
Section: Brachyury Function At the Blastoporementioning
confidence: 99%
“…The ring-shaped expression of Brachyury in the blastula marginal zone disappears, to be replaced later by expression in the constricting blastopore; still later, after blastopore closure, Brachyury expression appears in the prospective notochord, suggesting that a tri-phasic Brachyury expression pattern could be ancestral for anurans. In the urodeles Cynops and Ambystoma, Brachyury is expressed late, after the Gscexpressing anterior mesoderm has involuted, but in time for the involution of the Brachyury-expressing posterior mesoderm (Kaneda et al, 2009;Swiers et al, 2010). It remains to be determined, however, whether a role in germ layer internalization is indeed a common feature of the amphibian or even the metazoan Brachyury gene.…”
Section: Brachyury Function At the Blastoporementioning
confidence: 99%
“…At the yolk-plug stage, Cybra expression is restricted to involuted and elongated notochord and surface presumptive tail mesoderm around the blastopore (Sone et al, 1997;Doi et al, 2000;Kaneda et al, 2009). At the neurula stage, Cybra expression is detected in the entire notochord (Figs.…”
Section: Gene Expression Domains Of the Early Gastrula Dmzmentioning
confidence: 98%
“…It has been demonstrated that the vegetal (lower) half of the Cynops early gastrula DMZ (LDMZ) forms the anterior half of the ARF that self-differentiates only into endodermal tissues, such as pharyngeal endoderm (Kaneda et al, 2009). The animal (upper) half of the DMZ (UDMZ) forms the entire notochord after involution.…”
Section: Cynops Pyrrhogaster and Other Urodelesmentioning
confidence: 99%
See 2 more Smart Citations